Low-temperature structures of Prussian blue analogues for electrochemical applications - Dr Hanna Boström; Dr Ron Smith; Dr William Brant (ISIS Facility, 2019)
We propose a low-temperature diffraction study at POLARIS of Prussian blue analogues (PBAs) of general formula NaxMM'(CN)6, where 1 < x 2. These systems currently attract intense research interest due to their potential applications as electrodes in sodium ion batteries. In order to fully understand the electrochemical processes, accurate structural models are vital. At present, the most favourable position of Na in the framework is debated and we believe that this diffraction study will be an important contribution to this discussion. Moreover, high Na content yields distortions of the metal-cyanide framework---analogous to octahedral tilting in perovskites. We aim to investigate the thermal response of the tilting, which currently is an underexplored area, in contrast to the work on tilting in perovskites. Our study is thus relevant to both applied and fundamental chemistry.
Keywords: STFC ISIS Neutron and Muon Data